Advanced abdominal imaging with dual energy CT is feasible without increasing radiation dose. Issue 1 (December 2016) - Uhrig, Monika; Simons, David; Kachelrieß, Marc; Pisana, Francesco; Kuchenbecker, Stefan; Schlemmer, Heinz-Peter
Abstract Background Dual energy CT (DECT) has proven its potential in oncological imaging. Considering the repeated follow-up examinations, radiation dose should not exceed conventional single energy CT (SECT). Comparison studies on the same scanner with a large number of patients, considering patient geometries and image quality, and exploiting full potential of SECT dose reduction are rare. Purpose of this retrospective study was to compare dose of dual source DECT versus dose-optimized SECT abdominal imaging in clinical routine. Methods One hundred patients (62y (±14)) had either contrast-enhanced SECT including automatic voltage control (44) or DECT (56). CT dose index (CTDIvol), size-specific dose-estimate (SSDE) and dose-length product (DLP) were reported. Image noise (SD) was recorded as mean of three ROIs placed in subcutaneous fat and normalized to dose by S D n = S D × CDTIvol SDn=SD× CDTIvol . For dose-normalized contrast-to-noise ratio (CNRD), mean attenuation of psoas muscle (CTmuscle ) and subcutaneous fat (CTfat ) were compared byCNRD = (CTmuscle − CTfat )/SDn . Statistical significance was tested with two-sidedt -test (α = 0.05). Results There was no significant difference (p < 0.05) between DECT and SECT: Mean CTDIvol was 14.2 mGy (±3.9) (DECT) and 14.3 mGy (±4.5) (SECT). Mean DLP was 680 mGy*cm (±220) (DECT) and 665 mGy*cm (±231) (SECT). Mean SSDE was 15.7 mGy (±1.9) (DECT) and 16.1 mGy (±2.5) (SECT). Mean SDn was 42.2 (±13.9) HU * mGy *mGy (DECT) and 47.8 (±14.9) HU * mGy *mGy (SECT). Mean CNRD was 3.9 (±1.3) mGy − 1 2 mGy^-12 . (DECT) and 4.0 (±1.3) mGy − 1 2 mGy^-12 (SECT). Conclusion Abdominal DECT is feasible without increasing radiation dose or deteriorating image quality, even compared to dose-optimized SECT including automatic voltage control. Thus DECT can contribute to sophisticated oncological imaging without dose penalty.